2018
DOI: 10.7573/dic.212552
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual allergen immunotherapy for respiratory allergy: a systematic review

Abstract: The objective of the systematic review is to provide complete and updated information on efficacy and safety of sublingual immunotherapy (SLIT) formulations for the treatment of allergic respiratory diseases (ARDs). The literature search was conducted on PubMed database, involving double-blind, randomized clinical trials published between January 1992 and 2018, written in English, and performed in humans. The number of articles finally selected for review was 112. Data from the majority of properly controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 121 publications
0
21
0
Order By: Relevance
“…The SLIT-tablets have been developed for the treatment of grass pollen-induced AR and HDMinduced AR but the allergen content and dosing have not been standardized to date. The varied content among different products also affects the guidelines [15]. In addition, a limitation of SLIT tablet occurs from its ingredient which consists of only one antigen [14].…”
Section: General Methods and Novel Approaches Of Administrationmentioning
confidence: 99%
“…The SLIT-tablets have been developed for the treatment of grass pollen-induced AR and HDMinduced AR but the allergen content and dosing have not been standardized to date. The varied content among different products also affects the guidelines [15]. In addition, a limitation of SLIT tablet occurs from its ingredient which consists of only one antigen [14].…”
Section: General Methods and Novel Approaches Of Administrationmentioning
confidence: 99%
“…Many controlled clinical trials have shown the efficacy and safety of AIT in allergic asthma for adults and children, with both findings confirmed by a recently published meta‐analysis . In particular, the impact of AIT on the treatment of asthma in children has been investigated by several randomized controlled trials with variable results due to the heterogeneity of tested products and clinical outcomes.…”
mentioning
confidence: 86%
“…In particular, the impact of AIT on the treatment of asthma in children has been investigated by several randomized controlled trials with variable results due to the heterogeneity of tested products and clinical outcomes. However, a consistent reduction in combined rhinitis and asthma symptom and medication scores, as well as in rescue medication use, have been demonstrated in pediatric patients with asthma and comorbid AR treated with AIT . These clinical effects have been also demonstrated to be persistent after AIT discontinuation: A prospective study showed a reduction in the presence of asthma, number of patients using asthma medications, use of bronchodilator, and peak expiratory flow rate in asthmatic children treated with HDM SLIT after 5 years of discontinuation, compared with controls .…”
mentioning
confidence: 91%
“…The risk of adverse systemic reactions was found to be higher after subcutaneous administration of immunotherapy in comparison with placebo. Another meta-analysis (117) reported modest benefits of sublingual immunotherapy in patients with mild-to-moderate asthma.…”
Section: Immunotherapymentioning
confidence: 99%